Empowering Communities Through Household Organic Waste Management: A Case Study in Kajartengguli Village, Indonesia - Inggit Marodiyah; Atikha Sidhi Cahyana; Intan Rohma Nurmalasari (Indonesian Journal of Cultural and Community Development, 2023)
Household waste, particularly solid waste, poses significant environmental challenges globally, impacting land, water, and air quality. This study aims to address the environmental degradation caused by waste accumulation by implementing a simple waste management approach in Kajartengguli Village, Indonesia. The method involves segregating household waste into organic and inorganic categories, with a focus on the composting of organic waste. By providing socialization and training sessions, the local community, specifically the PKK (Family Welfare Movement) members, were educated about waste management practices and trained in composting techniques. The outcomes revealed that this community engagement initiative increased waste management knowledge and empowered the residents to reduce household waste, particularly in Kajartengguli Village. The program's success lies in its ability to transform organic waste into compost, which not only improves soil fertility but also provides economic benefits through the sale of compost products. The implications of this study highlight the importance of community-driven waste management initiatives in mitigating the global waste crisis and promoting environmental stewardship. Highlight: Household waste management is crucial for mitigating the global waste crisis and reducing environmental pollution. Effective waste management involves segregating organic and inorganic waste, with a focus on composting organic waste. Community engagement programs can empower residents by increasing their knowledge and awareness of waste management practices, promoting the utilization of organic waste as compost, and reducing the population of household waste in the surrounding environment. Keyword: Household Waste Management, Organic Waste, Composting, Community Engagement, Environmental Stewardship